Penyampaian Dakwah Islam di Media Sosial Bagi Generasi Z: Penyampaian Dakwah Islam di Media Sosial Bagi Generasi Z - Silviana Putri Kusumawati (Institut Agama Islam (IAI) Nurul Hakim, 2022)
Generation Z is the generation that was born when there was progress in science and technology. The development of science and technology has resulted in the rapid growth of information in the social media. Humans in this generation Z tend to be more aware of the available technology. Various technologies available allow the transfer of knowledge using social media. The use of mass media certainly has positive and negative effects. One of the positive effects of the use of social media is the broadcasting of Islamic da'wah in the social media. This Islamic da'wah broadcast through various mass media platforms, such as Instagram, YouTube, Tik-Tok, Podcast, Twitter to Facebook. The delivery of Islamic da'wah through social media invites enthusiasm for Generation Z to listen and see Islamic da'wah in the social media. Generation Z almost every day uses social media. Thus, the various da'wah presented in the social media can be used as an effort to broadcast Islam. This study examines the delivery of Islamic da'wah through mass media using descriptive qualitative research methods with literature studies. So that the resulting data comes from scientific journals which are then compiled using valid theoretical sentences.